The rise and phenomenal growth of Samuel Mutendi’s Zion christian church in the Shangwe area. - Mberengwa, Norman (Midlands State University, 2018)
The research is grounded on an academic exploration of the rise and phenomenal growth of Samuel Mutendi’s Zion Christian Church in the Shangwe area. The research was stimulated by the puzzling rise and phenomenal growth of ZCC which has led to the decline of mainline churches; a situation that has led to speculations that the ZCC is using magic charms to get coverts. The research examines the factors which contributed to the rise of ZCC in the Shangwe area. A typology which was sought clarify the factors dichotomized the factors into political, psychological, pneumatological, economic, cosmological, numinological, organizational, liturgical, and sociological dimensions. The background of the area under study was explored at great length.